1997
DOI: 10.1089/aid.1997.13.97
|View full text |Cite
|
Sign up to set email alerts
|

Human Plasmatic Apolipoprotein H Binds Human Immunodeficiency Virus Type 1 and Type 2 Proteins

Abstract: Apolipoprotein H (apo H), isolated from human plasma albumin solution, was shown to capture HIV-1-related antigens from antigen-positive sera (HIV-1 AG+) of AIDS patients, by using HIV-1-specific polyclonal antibodies. In an enzyme-linked immunosorbent assay and ligand blot and dot assays, apo H was able to bind recombinant retroviral HIV antigens, especially Gag proteins p18 of HIV-1, p26 of HIV-2, and Env gp160 of HIV-1. Binding was shown to be pH and NaCl dependent, with an optimum at acidic pH and low ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…ApoH was purified from human plasma albumin solutions as previously described (46) and used to coat magnetic beads (Merck Chimie S.A.S., Paris, France) and ELISA plates (96-well flat-bottom microplates). ApoH-coated magnetic beads and plates used in this study were supplied by ApoH Technologies S.A. (Villeneuve Saint Georges, France).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ApoH was purified from human plasma albumin solutions as previously described (46) and used to coat magnetic beads (Merck Chimie S.A.S., Paris, France) and ELISA plates (96-well flat-bottom microplates). ApoH-coated magnetic beads and plates used in this study were supplied by ApoH Technologies S.A. (Villeneuve Saint Georges, France).…”
Section: Methodsmentioning
confidence: 99%
“…Several reports show that ApoH also interacts with viral proteins, such as the hepatitis B virus (HBV) antigen and proteins p18, p26, and gp160 of the human immunodeficiency virus (12,30,46,47). Interestingly, studies involving binding to the HBV antigen suggest that ApoH specifically binds DNAcontaining HBV particles, thus discriminating, through an undefined mechanism, between active replicating virus and empty noninfectious particles (47).…”
mentioning
confidence: 99%
“…These data strongly suggest that viral phospholipids are involved in the ApoH-HBV/HBsAg interaction. It has been also shown that ApoH interact with antigens of human immunodeficiency virus (HIV) types I and II, particularly the Gag proteins of HIV 1 and 2 of p18 and p26 of HIV-1 HIV-2 or of gp160 of HIV-1 (Stefas et al, 1997), suggesting that the interaction of ApoH with HIV proteins may result in part from the ApoH affinity for PL. According to Stefas et al (1997), experimental conditions, such as acidic pH and/or the presence of detergent, could lead to conformational changes of ApoH or viral proteins thereby inducing the binding between ApoH and HIV-1.…”
Section: The Use Of Apoh For Drastic Improvement Of Viral Detectionmentioning
confidence: 99%
“…Beta2-glycoprotein I (Agar et al, 2011), also known under the name of Apolipoprotein H (ApoH) is one of the acute phase proteins exhibiting the most striking scavenger properties, strikingly is able to catch early apoptotic cells in a Ca2+-independent manner(d 'Angeac et al, 2005). This protein traps every kind of pathogenic microorganisms, including parasites (examples: Leishmania donovani, Plasmodium falciparum, etc), Gram + or Gram -bacteria (Escherichia coli, Salmonella, Listeria monocytogenes, Staphylococcus aureus, etc) and RNA or DNA enveloped or non-enveloped viruses (Hepatitis B, Hantaviruses, HIV, Rotaviruses, and others viruses) (Godoy et al, 2009;Stefas et al, 1997;Stefas et al, 2001). In addition, products of the complement pathways, in turn, promote inflammation; chemoattract phagocytes to the infected zone, also attach microbes to phagocytes, and finally induce cytolysis of infected cells.…”
Section: Fig 2 Damps As Inducers Of the Aprmentioning
confidence: 99%